2015
DOI: 10.3389/fnhum.2015.00138
|View full text |Cite
|
Sign up to set email alerts
|

Experience, cortisol reactivity, and the coordination of emotional responses to skydiving

Abstract: Physiological habituation to laboratory stressors has previously been demonstrated, although the literature remains equivocal. Previous studies have found skydiving to be a salient naturalistic stressor that elicits a robust subjective and physiological stress response. However, it is uncertain whether (or how) stress reactivity habituates to this stressor given that skydiving remains a risky, life-threatening challenge with every jump despite experience. While multiple components of the stress response have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 48 publications
9
43
0
Order By: Relevance
“…There was a greater increase in cortisol levels in response to stress in the men than in the women, as reported elsewhere [56] Another report showed that experienced individuals had a lower increase in cortisol levels and faster recovery compared to those without experience [57]. Although we did not demonstrate an effect of experience, that the longer experience of the female emergency medical dispatchers may have affected the results.…”
Section: Discussionsupporting
confidence: 75%
“…There was a greater increase in cortisol levels in response to stress in the men than in the women, as reported elsewhere [56] Another report showed that experienced individuals had a lower increase in cortisol levels and faster recovery compared to those without experience [57]. Although we did not demonstrate an effect of experience, that the longer experience of the female emergency medical dispatchers may have affected the results.…”
Section: Discussionsupporting
confidence: 75%
“…Our findings are conclusive in showing that thrill experiences like a tandem skydive should not be suggested as a possible treatment for anhedonia, as the skydive did not provide the hypothesized motivational boost to kick start the implementation of the lifestyle advice. Possibly, a tandem skydive is only effective in increasing immediate pleasure and motivation, as was found in previous studies (Meyer et al, 2015;Wang & Tsien, 2011), and does not have a persistent effect. Our lack of effects may indicate that a skydive is not effective in decreasing anhedonia.…”
Section: Discussionmentioning
confidence: 52%
“…Even though it is considered to be safe, falling from a great height evokes a substantial fight-flight response in virtually all individuals (Hare, Wetherell, & Smith, 2013). Physiologically, skydiving results in increases in heart rate, blood pressure, and alpha-amylase and cortisol levels (Chatterton et al, 1997;Hare et al, 2013;Meyer et al, 2015). Psychologically, individuals experience extreme fear before and during the free fall experience (Hare et al, 2013), followed by euphoria afterwards (Meyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 However, the peak cortisol concentration before sky-diving is not different between experienced versus less experienced sky-divers 9 where the pattern of cortisol reactivity (eg, quick rise and reduction) is distinct. 10 Therefore, it is anticipated that age and experience might play a greater role in the pattern of cortisol reactivity than in the magnitude of the cortisol response.…”
Section: Introductionmentioning
confidence: 99%